1995
DOI: 10.1111/j.1365-2249.1995.tb08365.x
|View full text |Cite
|
Sign up to set email alerts
|

Human recombinant IL-4 decreases the emergence of non-specific cytolytic cells and favours the appearance of memory cells (CD4+CD45RO+) in the IL-2-driven development of cytotoxic T lymphocytes against autologous ovarian tumour cells

Abstract: SUMMARYAs IL-4 and IL-6 have also been reported to promote the development ofT lymphocytes such as IL-2, we investigated their role in the development of specific cytotoxic T lymphocytes (CTL) against autologous ovarian tumours in mixed lymphocyte tumour cultures (ML TC). Peripheral blood lymphocytes (PBL) from five ovarian carcinoma (OC) patients were incubated with autologous OC cells at a PBL:OC cell ratio of 20:1 in IL-2 alone (50 Urml for the first week and 200 U/ml thereafter) or with IL-4 (100 U/ml) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

1999
1999
2003
2003

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…The results presented here show that in cells triggered by IL-12, even more CD26 and CD45R0 proteins are associated. Although some interleukins can regulate CD45 isoforms (52,53), the close CD26-CD45R0 association was seen only with IL-12. Taking these results together with those of in vivo elimination of rafts and CD26 expression inhibition, it can be concluded that the new surface CD26 molecules are directed to the soluble fraction near the lipid raft core and anchor CD45R0.…”
Section: Discussionmentioning
confidence: 99%
“…The results presented here show that in cells triggered by IL-12, even more CD26 and CD45R0 proteins are associated. Although some interleukins can regulate CD45 isoforms (52,53), the close CD26-CD45R0 association was seen only with IL-12. Taking these results together with those of in vivo elimination of rafts and CD26 expression inhibition, it can be concluded that the new surface CD26 molecules are directed to the soluble fraction near the lipid raft core and anchor CD45R0.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, IL-4 or IFN-γ seems to be necessary or at least to augment the IL-2-mediated activation of CTLs in many other systems. 17,[22][23][24] Although the mechanisms involved in this discrepancy are unclear at present, the antigens used in the relevant experiments were different from each other. We used a peptide from a self antigen preferentially expressed in cancer cells, while others have used peptides from other tumor-rejection antigens, exogenous antigens, or tumor cells alone.…”
Section: Discussionmentioning
confidence: 99%
“…Although there have been a large number of studies in this field, the differences in the mechanisms by which peptides induce CTLs appear to be significant. 13,[16][17][18][19][20][21][22][23][24][25][26] Identification of the cytokine combinations required for optimal CTL induction by these peptides will be important in developing a better understanding of the cellular and molecular basis of tumor-specific immunity, and for peptide-based specific immunotherapy. Therefore, we have investigated in this study the cytokine combinations required for the induction of HLA-class I-restricted and tumor-specific CTLs by a SART1-derived peptide.…”
mentioning
confidence: 99%
“…MLTC was performed for 7 days in ASF104 medium supplemented with 1% human albumin. On day 1, recombinant interleukin-4 (Dainippon) at 10 U/ml was added, to inhibit lymphokineactivated killer cell induction [15], and recombinant interleukin-2 (Shionogi, Osaka, Japan) at 400 IU/ml was added on day 3. At the end of the culture period, live cells were collected by Ficoll-Hypaque density-gradient centrifugation, washed, and used as effector cells.…”
Section: Induction Of Ctlmentioning
confidence: 99%